The progression of salt‐wasting and the body weight change during the first 2 weeks of life in classical 21‐hydroxylase deficiency patients. (20th October 2020) - Gau, Maki; Konishi, Kaoru; Takasawa, Kei; Nakagawa, Ryuichi; Tsuji‐Hosokawa, Atsumi; Hashimoto, Atsuko; Sutani, Akito; Tajima, Toshihiro; Hasegawa, Tomonobu; Morio, Tomohiro; Kashimada, Kenichi
Abstract: Background: One of the major purposes of newborn screening for 21‐hydroxylase deficiency (21OHD) is preventing life‐threatening adrenal crisis. However, the details of adrenal crisis in newborns are not precisely documented. Aim: We aimed to clarify the clinical details of salt‐wasting in newborn 21OHD patients. Methods: Based on the follow‐up survey of the screening in Tokyo from 1989 to 2017, we retrospectively analysed the conditions of classical 21OHD neonates before the initiation of therapy. Results: One hundred classical 21OHD patients (55 male, 45 female) were analysed. The age at the first hospital visit was 0–20 days with sex difference (male: 9.0 ± 3.5 days; female: 6.2 ± 3.9 days). Thirty‐seven (37.4%) patients exhibited severe salt‐wasting (SSW), that is, Na < 130 mEq/L, K > 7 mEq/L or Na/K ratio < 20; except for one case, SSW developed in or after the second week of life. The serum concentrations of Na, K and Na/K were linearly correlated with age in days ( R 2 = .38, .25, and .34 respectively), suggesting that the risk of SSW increases linearly without a threshold. The age at which the regression lines reached Na < 130 mEq/L, K > 7 mEq/L and Na/K < 20 was approximately coincided, 11.1, 12.3 and 11.2 days, respectively. All SSW patients exhibited decreased body weight from birth in their second week of life. Conclusion: Our data revealed that the risk of developing SSW increases during the second week of life without a threshold, and for preventing SSW, early intervention, ideally during first week of life, is desirable. An increased body weight in the second week of life indicates the absence of SSW.